Longitudinal associations of active renal disease with irreversible organ damage accrual in systemic lupus erythematosus. (December 2019) - Kandane-Rathnayake, R; Kent, J R; Louthrenoo, W; Luo, S -F; Wu, Y -JJ; Lateef, A; Golder, V; Sockalingam, S; Navarra, S a; Zamora, L; Hamijoyo, L; Katsumata, Y; et al.
Objective: To examine longitudinal associations of active lupus nephritis with organ damage accrual in patients with systemic lupus erythematosus (SLE). Methods: This study was performed using data from a large multinational prospective cohort. Active lupus nephritis at any visit was defined by the presence of urinary casts, proteinuria, haematuria or pyuria, as indicated by the cut-offs in the SLE Disease Activity Index (SLEDAI)-2K, collected at each visit. Organ damage accrual was defined as a change of SLICC-ACR Damage Index (SDI) score >0 units between baseline and final annual visits. Renal damage accrual was defined if there was new damage recorded in renal SDI domains (estimated glomerular filtration rate <50%/proteinuria >3.5 g per 24 h/end-stage kidney disease). Time-dependent hazard regression analyses were used to examine the associations between active lupus nephritis and damage accrual. Results: Patients ( N = 1735) were studied during 12, 717 visits for a median (inter-quartile range) follow-up period of 795 (532, 1087) days. Forty per cent of patients had evidence of active lupus nephritis at least once during the study period, and active lupus nephritis was observed in 3030 (24%) visits. Forty-eight per cent of patients had organ damage at baseline and 14% accrued organ damage. Patients with active lupus nephritis were 52% more likely to accrue any organ damage compared with those without active lupus nephritis (adjusted hazard ratio = 1.52 (95% confidence interval (CI): 1.16, 1.97), p < 0.02). Active lupus nephritis was strongly associated with damage accrual in renal but not in non-renal organ domains (hazard ratios = 13.0 (95% CI: 6.58, 25.5) p < 0.001 and 0.96 (95% CI: 0.69, 1.32) p = 0.8, respectively). There was no effect of ethnicity on renal damage accrual, but Asian ethnicity was significantly associated with reduced non-renal damage accrual. Conclusion: Active lupus nephritis measured using the SLEDAI-2K domain cut-offs is associated with renal, but not non-renal, damage accrual in SLE.